Variation in Alcohol Policy Enforcement Across Urban and Nonurban Communities. Issue 2 (12th September 2019) - Calvert, Collin; Toomey, Traci; Lenk, Kathleen; Joshi, Spruha; Nelson, Toben; Erickson, Darin
Abstract: Purpose: The goal of this study was to assess whether different types of communities (ie, urban, suburban, small town, and rural) vary in the alcohol enforcement activities they conduct. Methods: We conducted a cross‐sectional study using data from a national survey of local law enforcement agencies. Data: The survey assessed enforcement of a range of alcohol policies at 1, 082 law enforcement agencies. U.S. Census data were used to categorize agencies based on community type. Results: Agencies in urban areas conducted more enforcement activities than agencies in other community types. Urban agencies were more likely than rural agencies to conduct underage compliance checks (prevalence ratio [PR]: 0.42; CI: 0.34‐0.53), saturation patrols (PR: 0.80; CI: 0.67‐0.95), sobriety checkpoints (PR: 0.68; CI: 0.53‐0.86), and enforcement aimed at illegal sales to intoxicated patrons (PR: 0.59; CI: 0.42‐0.81). Urban agencies were also more likely than small town agencies to do compliance checks (PR: 0.66; CI: 0.56‐0.79) and sobriety checkpoints (PR: 0.75; CI: 0.61‐0.91), and they were more likely than suburban agencies to do compliance checks (PR: 0.67; CI: 0.57‐0.78) and enforcement actions around the sale of alcohol to intoxicated patrons (PR: 0.64; CI: 0.45‐0.90), provision of alcohol to minors (PR: 0.77; CI: 0.65‐0.92), and consumption by minors (PR: 0.90; CI: 0.82‐0.99). Conclusions: Enforcement of alcohol laws differs by community type. Future research is needed to identify mechanisms to increase enforcement by agencies in different types of communities.